Positioning Islamic social enterprise (ISE) / Nurul Aini Muhamed, Muhammad Iqmal Hisham Kamaruddin and Nur Syazwani Nasruddin - Muhamed, Nurul Aini; Kamaruddin, Muhammad Iqmal Hisham; Nasruddin, Nur Syazwani (Universiti Teknologi MARA Selangor, 2018)
The Islamic Social Enterprise (ISE) is increasingly gaining attention due to its flexibility to perform trading activities for income generation while at the same time offering societal contributions. The roles of ISE is greatly viewed from value-based perspective, where the ISE's objective is to support the Islamic third economic sector in easing the needs of those unfortunate and middle class citizens. Involving in trading activities is imperative for this institution given that collections from donations are insufficient as the demand for contribution is very high, as well as there is some cost acquired in its management. In this case, ISE's sustainability should be taking care of to ensure the continuous contributions can be given to society. There are several perspectives on the definition of ISE since it is normally formatted in different forms, receiving initial and continuous source of collections from different Islamic charitable contracts and running different activities. Therefore, this paper attempts to position the definition and the context of ISE by deliberating its definitions and characteristics. Thus, the paper reviews the existing literature from the area of Islamic third economic sector and Islamic transaction law and inter-relating these aspects in the context of ISE. The focus is given on the aspect of the institution's objectives, source of capital using the Islamic charitable contracts, its activities and; income generation and distribution. Based on the findings, the distinctive yet flexible definition of ISE expands the new and relevant area of Islamic third economic sector using Islamic charitable contracts. The discussion highlights that ISE should be guided by maqasid shariah, and follow the Islamic principles. This paper points out that not all Islamic charitable contracts are applicable for ISE, which should be comprehended for new established ISE.